Computed tomography-guided transfacial buccal space core biopsy of deep head and neck space lesions: our experience. Issue 10 (December 2021) - Couzins, M.; Ali, R.; Mitchell, O.; Brennan, P.A.; Bekker, J.
Abstract: Deep head and neck space lesions can present a number of diagnostic challenges due to their deep anatomical position and difficult access for diagnostic tissue sampling. We describe a series of percutaneous 'transfacial' buccal space computed tomography (CT)-guided core biopsies of these lesions and subsequent histological findings. Six patients underwent CT-guided core biopsy of deep parotid, parapharyngeal, or masticator space lesions over a 30-month period. We describe our biopsy technique and correlate our histological findings with subsequent surgical resection where performed. Five of six of CT-guided biopsies obtained sufficient tissue for histological interpretation with varying findings, including salivary gland tumours and squamous cell carcinoma confirmed on subsequent resection. One patient was treated palliatively following core biopsy. No biopsy-related complications were observed. In our small series, percutaneous CT-guided transfacial biopsy via the buccal space has proved an excellent option for the minimally invasive tissue acquisition of deep head and neck space lesions.